Fractal correlation property of heart rate variability in response to the postural change maneuver in healthy women - De Souza, Ana C.A.; Cisternas, José R.; De Abreu, Luiz Carlos; Roque, Adriano L. [UNESP]; Monteiro, Carlos B.M.; Adami, Fernando; Vanderlei, Luiz Carlos M. [UNESP]; Sousa, Fernando H. [UNESP]; Ferreira, Lucas L. [UNESP]; Valenti, Vitor E. [UNESP] (Springer Nature, 2014)
Background: We evaluated the effects of the PCM on the fractal analysis of the HRV in healthy women. Method. We evaluated healthy women between 18 and 30 years old. HRV was analyzed in the time (SDNN, RMSSD, NN50 and pNN50) and frequency (LF, HF and LF/HF ratio) domains as well as short and long-term fractal exponents (alpha-1 and alpha-2) of the detrended fluctuation analysis (DFA). HRV was recorded at rest for ten minutes at seated rest and then the women quickly stood up from a seated position in up to three seconds and remained standing for 15 minutes. HRV was recorded at the following time: rest, 0-5 min, 5-10 min and 10-15 min during standing. Results: We observed decrease (p < 0.05) in the time-domain indices of HRV between seated and 10-15 minutes after the volunteer stood up. The LF (ms2) and HF (ms2) indices were also reduced (p < 0.05) at 10-15 minutes after the volunteer stood up compared to seated while the LF (nu) was increased at 5-10 min and 10-15 min (p < 0.05). The short-term alpha-1 exponent was increased (p < 0.05) at all moments investigated compared to seated. Increase in the properties of short-term fractal correlations of heart rate dynamics accompanied by a decrease in the parasympathetic modulation and global HRV was observed in response to the postural change maneuver. Conclusion: We suggest that fractal analysis of HRV is more sensitive than frequency and time-domain analysis of HRV during the postural change maneuver. © 2014 de Souza et al.; licensee BioMed Central Ltd.
Keywords: Autonomic nervous system; Cardiovascular system; Nonlinear dynamics; Physiology